Barriers to Tourism Travel Service Business Cooperation with Pioneering Tourism Villages in Tabanan Regency - Bagus Gede Wiliam Pranata Kesuma; I Nyoman Sukma Arida; Ni Made Sofia Wijaya (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Tourism villages in Bali Province have reached 37.26% of the existing villages and only 2 are in the independent category. Tabanan Regency has a number of pilot tourism villages and the majority are more than five years old. Obstacles to increasing the status of a tourist village are thought to occur due to the lack of tourists and the ability of managers to cooperate with the tourism industry. Research needs to be done to overcome barriers to the establishment of cooperation between tourism villages and industry. The problems described need to be solved by formulating a strategy. The pilot Tourism Village which is the location of the research focus has great potential but has experienced obstacles. This study aims to: analyze the role of Tourism Travel business(1), barriers to cooperation between tourism travel business and pilot Tourism Village(2), and develop a management strategy of pilot tourism village in Tabanan Regency(3). This study used qualitative descriptive method. The Data was obtained through in-depth interviews with eight experts. Obstacles are described using coding techniques and then strategies are made to overcome them. The strategy was prepared using Intepretive Structural Modeling analysis techniques. The results showed that UPW has a role in assessing cooperation proposals consisting of details of tourist activities offered, equipment required, price details, feed back, matching proposal descriptions, uniqueness, service quality, cleanliness, and safety. Barriers to cooperation occur due to the location of the tourist village, the potential benefits of the formation of cooperation, and tourist interest. The strategies formed to overcome these obstacles are increasing the competence of human resources in Pilot tourism villages, packaging of industry-standard tourism products, accelerating cooperation between tourism villages and the tourism industry. Suggestions in this study is the implementation of a strategy that is in accordance with the strategy model that has been formed.